2019
DOI: 10.1074/jbc.ra118.006022
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidase 1–mediated desialylation of the mucin 1 ectodomain releases a decoy receptor that protects against Pseudomonas aeruginosa lung infection

Abstract: Pseudomonas aeruginosa (Pa) expresses an adhesin, flagellin, that engages the mucin 1 (MUC1) ectodomain (ED) expressed on airway epithelia, increasing association of MUC1-ED with neuraminidase 1 (NEU1) and MUC1-ED desialylation. The MUC1-ED desialylation unmasks both cryptic binding sites for Pa and a protease recognition site, permitting its proteolytic release as a hyperadhesive decoy receptor for Pa. We found here that intranasal administration of Pa strain K (PAK) to BALB/c mice increases MUC1-ED shedding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 77 publications
4
50
0
Order By: Relevance
“…In another study, it was shown that the immunosuppressive effect of MUC1 on TLR5 in bronchial epithelial cells is mediated by prevention of recruitment of MyD88 to TLR5 and inhibition of downstream signaling ( 34 ). A recent study reported that the extracellular domain of MUC1 can act as a releasable decoy molecule during P. aeruginosa infection, thereby restricting pathogen adherence to the epithelial surface ( 35 ).…”
Section: Functions Of Transmembrane Mucin During Respiratory Infectiomentioning
confidence: 99%
“…In another study, it was shown that the immunosuppressive effect of MUC1 on TLR5 in bronchial epithelial cells is mediated by prevention of recruitment of MyD88 to TLR5 and inhibition of downstream signaling ( 34 ). A recent study reported that the extracellular domain of MUC1 can act as a releasable decoy molecule during P. aeruginosa infection, thereby restricting pathogen adherence to the epithelial surface ( 35 ).…”
Section: Functions Of Transmembrane Mucin During Respiratory Infectiomentioning
confidence: 99%
“…Infection with P. aeruginosa strain K in mice increased Muc1 expression in BAL compared to sham infection [55]. Muc1 −/− mice had reduced colonization of P. aeruginosa (p<0.05) due to increased clearance by heightened early inflammatory responses to the infection, compared to wild-type mice [60].…”
Section: P Aeruginosamentioning
confidence: 91%
“…P. aeruginosa engages the MUC1 ectodomain through its adhesin, flagellin [55,56]. In primary human alveolar macrophages isolated from the BAL of healthy subjects and human monocytic cell line (THP-1 cells), P. aeruginosa infection significantly increased MUC1 expression compared to uninfected cells [57].…”
Section: P Aeruginosamentioning
confidence: 99%
“…Decoy peptides are applied throughout various fields of research and have been demonstrated as an anticancer agent via a decoy receptor for Wnt ligands [ 34 , 36 ]. Importantly, decoy receptors constitute a novel and relatively unknown target for development of antiviral drugs [ 37 ] or as a therapeutic tool for inhibition of bacterial infections [ 38 ]. Moreover, decoy peptides are employed as a novel class of therapeutics for combatting neurotoxic envenoming [ 39 ].…”
Section: Decoymentioning
confidence: 99%